From Westernisation To Wild Westernisation: The Power Of Social Media - Nur Esra Atmaca (Yeni Medya)
The 21st century draws attention as the history of rapid social changes as well as technology. The phenomenon of westernisation as an important expression of development and modernisation in the historical process is accepted as an important scope of human rights and freedom of expression. The fact that the newspaper, as the first mass media, began to reach people in the 17th century brought the expanding effect of freedom of expression on the masses to the agenda. During the following 300 years, the means of reaching the masses have continuously developed and diversified. Although the limits of freedoms vary from society to society, the gains have been recognised as a universal necessity with the concepts of human rights, the right to information and freedom of expression. The important breaking point is the unprecedented power and function of the Internet, which is characterised as the 5th power, in reaching the masses. With people becoming producers in a medium for the first time, a media medium has faced new problems brought about by ‘limitlessness’; the internet has not been able to guarantee the maintenance of a democratic environment. In this study, it is examined how westernisation, which means reaching the level of development of western countries worldwide, has revealed experiences with enriched media and how it has become a danger area by turning into a wild west environment. While offering important perspectives on social media, the study aims to bring to the fore that the sanctity of human life is as important as the unlimited freedom of these platforms. This study invites readers to a discussion on social media.